2016
DOI: 10.1007/s10935-016-0461-4
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use Prevention for Urban American Indian Youth: A Efficacy Trial of the Culturally Adapted Living in 2 Worlds Program

Abstract: This article describes a small efficacy trial of the Living in 2 Worlds (L2W) substance use prevention curriculum, a culturally adapted version of keepin’ it REAL (kiR) redesigned for urban American Indian (AI) middle school students. Focused on strengthening resiliency and AI cultural engagement, L2W teaches drug resistance skills, decision making, and culturally grounded prevention messages. Using cluster random assignment, the research team randomized three urban middle schools with enrichment classes for A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 45 publications
2
31
0
6
Order By: Relevance
“…Several studies have shown the efficacy of Environmental Prevention strategies to reduce community alcohol problems, including underage drinking, by reducing commercial alcohol availability (Holder et al, 2000;Treno, Gruenewald, Lee, & Remer, 2007;Treno & Lee, 2002;Wagenaar, Toomey, & Erickson, 2005). However, few investigators have described interventions on alcohol use among AI/AN youths (see Cheadle et al, 1995;Gabriel, Leichtling, Bolan, & Becker, 2013;Kulis, Ayers, & Harthun, 2017;May & Moran, 1995;Usera, 2017;Wagenaar, Livingston, Pettigrew, Kominsky, & Komro, 2018;Whitesell et al, 2012;Williams & Perry, 1998). A few studies have included AI/ANs in the study design but were not powered to test for effects that might be specific to the AI/AN sample (Livingston et al, 2018;Perry et al, 2000;Perry et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the efficacy of Environmental Prevention strategies to reduce community alcohol problems, including underage drinking, by reducing commercial alcohol availability (Holder et al, 2000;Treno, Gruenewald, Lee, & Remer, 2007;Treno & Lee, 2002;Wagenaar, Toomey, & Erickson, 2005). However, few investigators have described interventions on alcohol use among AI/AN youths (see Cheadle et al, 1995;Gabriel, Leichtling, Bolan, & Becker, 2013;Kulis, Ayers, & Harthun, 2017;May & Moran, 1995;Usera, 2017;Wagenaar, Livingston, Pettigrew, Kominsky, & Komro, 2018;Whitesell et al, 2012;Williams & Perry, 1998). A few studies have included AI/ANs in the study design but were not powered to test for effects that might be specific to the AI/AN sample (Livingston et al, 2018;Perry et al, 2000;Perry et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The pilot of the adapted program produced beneficial outcomes for substance resistance strategies (Kulis et al 2013). The efficacy trial showed improvements in substance-related knowledge, but no statistically significant improvements in substance resistance strategies or substance use frequency (Kulis et al 2016).…”
Section: Outcomes Type Setting and Context Of Prevention Programs Fmentioning
confidence: 95%
“…Cultural adaptation of non-Indigenous programs included translation of concepts into local Indigenous language and concepts, developing cultural images and the adaptation of activities to include cultural activities such as prayer, dancing and circle conversations. Three studies evaluated the Keepin' it REAL program: two were a cultural adaptation of this program called Living in 2 worlds (Kulis et al 2013;Kulis et al 2016), and one was unadapted (Dixon et al 2007). Dixon et al (2007) found iatrogenic outcomes for Indigenous adolescents, namely an increase in cannabis use following the program.…”
Section: Outcomes Type Setting and Context Of Prevention Programs Fmentioning
confidence: 99%
“…This model emphasizes personal self-management skills and the social skills to refuse drugs and to reduce motivation to use drugs. Kulis, Ayers, and Harthun's [52] project, Living in 2 Worlds (L2W), was adopted from the Keeping it Real program (KiR), a universal school-based substance use prevention program that teaches youth skills to resist substance Fig. 1 A flow chart-prisma diagram that illustrates the steps and outcomes of the scoping review use through the refuse, explain, avoid, and leave (R.E.A.L.)…”
Section: The Project Overviewmentioning
confidence: 99%
“…The L2W [52] project was adapted using a theoretical model of cultural adaptation that entailed adding culturally appropriate language, images, scenarios, and formats for urban Alaskan Indian youth while maintaining the core components of the KiR program. It also integrated three types of information: 1) prior research on substance use risk and protective factors, 2) culturally specific ways urban Alaskan Indian youth encounter and resist substance offers, and 3) Indigenous cultural elements.…”
Section: How the Projects Were Made Culturally Safementioning
confidence: 99%